Simulation of superhet retransmitting meter with analog-digital signal processing - Величко, Анатолий Федорович; Величко, Дмитрий Анатольевич; Величко, Сергей Анатольевич; Вичкань, Алексей Валерьевич; Клюева, Анна Николаевна; Нетребенко, Константин Владимирович (Eastern-European Journal of Enterprise Technologies, 2015)
Process control errors, caused by radio wave reflection from foreign objects, can be reduced by applying spatial filtering, implemented in a retransmitting method. Even greater benefits in measurements can be obtained using the superhet receivers and digital data processing techniques in this system. In the paper, a functional diagram of the superhet retransmitting meter with analog-digital processing was synthesized, a description of the main units was given. The mathematical formulas that determine the signal and wave conversions, occurring during operation of the measuring retransmitting system and processing of the received signals were presented. These formulas were written for previously unstudied operation cases of the measuring retransmitting system on the set of stable and fluctuating reflectors. Their application field is limited by the Fraunhofer zone. The main purpose of the mathematical description is a computer simulation of the processes occurring during the measurement and obtaining the statistical characteristics of the signals, received by the system. It is expected that using the formulas obtained, pseudo-random sequences of independent combinations of stable and fluctuating reflectors will be converted. The resulting mathematical description is the basis for computer simulation of the system under study and will allow to obtain and compare the statistical characteristics of the signals of the retransmitting system and radar sensor.